PREDIKSI SUHU TUBUH ORANGUTAN(Pongo pygmaeus wurmbii) BERDASARKAN SUHU FESES DI STASIUN PENELITIAN CABANG PANTI TAMAN NASIONAL GUNUNG PALUNG - junardi junardi; Slamet Rifanjani; Sofwan Anwari (Universitas Tanjungpura, 2019)
Orangutan body temperature prediction based on faeces temperature is done to determine the health condition of wild orangutans. The body temperature of orangutans in the wild is difficult to measure directly, the difficulty of measuring the body temperature of orangutans in the wild, so we need another method to be able to determine the body temperature of orangutans by measuring faecal temperature as a prediction of orangutan's body temperature in the wild. This research was carried out at the YIARI Rehabilitation site in Ketapang District and the Station Research Cabang Panti Gunung Palung National Park. The purpose of this study was to be able to predict the body temperature of orangutans based on faeces temperature at the Station Research Cabang Panti (SRCP). This study uses a non-invasive method or without measuring directly the object of research. Analysis of the study used simple linear regression using the SPSS and Microsoft Excel programs, prediction of the body temperature of orangutans in the wild was obtained based on the results of simple linear regression calculations at the YIARI rehabilitation site. Research results at the YIARI rehabilitation center were obtained by 10 individual orangutans. feces temperatures obtained an average between 33.4 ° C - 35.83 ° C and an average body temperature of 36.53 ° C - 37.5 ° C, so that the simple linear regression equation obtained is Y = 35.77 + 0.04X. There were 5 orangutans found at the Panti Branch Research Station. The results of orangutan's faecal temperature measurements average between 33.70 ° C-34.90 ° C, and prediction of orangutan body temperature between 37.12 ° C-37.17 ° C, with an average of 37.2 ° C.